A review study: the association between academic buoyancy and test anxiety - Li, Danwei; Ahmad, Nor Aniza; Roslan, Samsilah (Human Resources Management Academic Research Society (HRMARS), 2024)
Test anxiety is considered one of the most critical problems students face worldwide, and its prevalence is rising. Students' potential for poor academic performance may be exacerbated by test anxiety, which is widespread. Academic buoyancy, an emerging concept in positive psychology, is thought to be a protective factor for test anxiety. This study aims to summarize the results on the relationship between academic buoyancy and test anxiety by reviewing published studies including a sample of students from primary school to university. The results revealed that there is a significant correlation between academic buoyancy and test anxiety, and academic buoyancy is a crucial protective factor for test anxiety.